Assessing the Effect of Global Travel and Contact Restrictions on Mitigating the COVID-19 Pandemic. (July 2021) - Lai, Shengjie; Ruktanonchai, Nick W.; Carioli, Alessandra; Ruktanonchai, Corrine W.; Floyd, Jessica R.; Prosper, Olivia; Zhang, Chi; Du, Xiangjun; Yang, Weizhong; Tatem, Andrew J.
Abstract: Travel restrictions and physical distancing have been implemented across the world to mitigate the coronavirus disease 2019 (COVID-19) pandemic, but studies are needed to understand their effectiveness across regions and time. Based on the population mobility metrics derived from mobile phone geolocation data across 135 countries or territories during the first wave of the pandemic in 2020, we built a metapopulation epidemiological model to measure the effect of travel and contact restrictions on containing COVID-19 outbreaks across regions. We found that if these interventions had not been deployed, the cumulative number of cases could have shown a 97-fold (interquartile range 79–116) increase, as of May 31, 2020. However, their effectiveness depended upon the timing, duration, and intensity of the interventions, with variations in case severity seen across populations, regions, and seasons. Additionally, before effective vaccines are widely available and herd immunity is achieved, our results emphasize that a certain degree of physical distancing at the relaxation of the intervention stage will likely be needed to avoid rapid resurgences and subsequent lockdowns.